2017
DOI: 10.5815/ijmecs.2017.05.01
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Failing the Programming Skill Examination of Computing Students

Abstract: Abstract-This descriptive study utilized a validated instrument to determine the factors that affect failing a programming skill examination. Through this finding, the study attempted to provide solutions to address the concerns of the students. The top three reasons why students failed the programming skill examination were the insufficient time dedicated to programming courses, self-inefficacy in programming, and unmatched questiontime allotment. Overall, respondents attributed their failed mark in programmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…This paper is a description of a system of FOL based rules for the diagnosis and classification of skills, and the recommendation of learning path. The paper supports the application of the educational principle of chunking [4,5] in the diagnosis of students' skills for learning material recommendation in the learning of SQL: a subject that has been described as difficult. The structure of this paper continues with related work in Section II, and Section III SQL learning, teaching and assessment systems.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…This paper is a description of a system of FOL based rules for the diagnosis and classification of skills, and the recommendation of learning path. The paper supports the application of the educational principle of chunking [4,5] in the diagnosis of students' skills for learning material recommendation in the learning of SQL: a subject that has been described as difficult. The structure of this paper continues with related work in Section II, and Section III SQL learning, teaching and assessment systems.…”
Section: Introductionmentioning
confidence: 53%
“…Recent studies have also shown the factors affecting students' failure in programming. As one of the factors, [4] in their descriptive study identified inadequacy in the time dedicated to programming courses, that this consequently heralds to students' inability to match the degree of difficulty required in programming skills. Other factors attributed are lack of higher order thinking on the part of students and incomplete or inappropriate teaching processes [21], as well as the problem of selecting the correct teaching method or tool [22,4].…”
Section: Sql Learning Teaching and Assessment Systemsmentioning
confidence: 99%
“…Selecting the appropriate control structures (sequences, loops, conditionals, recursion, and repetition) for solving problems was also mentioned as one of the difficulties for novice students in higher education [32][33][34][35][36][37][38][39][40][41][42]. Bringula et al [43] found that most students failed the programming examination because the level of difficulty of the examination is not suitable to the students' level and allotted time. When they often cannot solve programming errors, they experience anxiety, panic, and stress [44].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Offline classroom teaching is divided into 16 hours. In classroom teaching, teachers focus on explaining the important knowledge points of the chapter, and students can bring the problems encountered in autonomous learning to the classroom for discussion [5]. At the same time, teachers can also rely on the learning network platform to publish difficult problems, practical problems and small case problems to organize students to make discussion speeches, and take students' classroom performance and online discussion records as the basis for classroom performance evaluation.…”
Section: The Reform Design Of the Curriculum Examination Modementioning
confidence: 99%